Bio-hyperbranched polyesters synthesized from citric acid and bio-polyols and applications on wood adhesives. (March 2023) - Jin, Tao; Zeng, Heyang; Huang, Yuefeng; Liu, Li; Yao, Wentao; Lei, Hong; Shi, Senlei; Du, Guanben; Zhang, Lianpeng
Abstract: Biomass-based adhesives have attracted extensive research interest in recent years as an effective alternative to formaldehyde-based adhesives which are non-renewable and harmful to human health. In this paper, citric acid-based hyperbranched polyester (HBPCA) resins were synthesized by green and simple strategy using natural citric acid (CA) and succinic anhydride (SA) as raw materials. Hyperbranched polyol (HBP) was prepared by nucleophilic addition reaction of SA with diethanolamine and later condensed with CA to produce HBPCA resins. The chemical structure of HBPCA resins was characterized using Fourier transform infrared spectroscopy (FTIR), 13 C nuclear magnetic resonance ( 13 C NMR), X-ray photoelectron spectroscopy (XPS), liquid chromatography−mass spectrometry (LC-MS), and gel permeation chromatography (GPC). The introduction of HBP enabled the resins to form a hyperbranched network cross-linked structure, which increased the cross-link density and thus prevented the intrusion of moisture. The results showed that HBPCA resin plywood has excellent adhesive strength and water resistance. The shear strength was 1.49 MPa and 1.47 MPa after immersion in hot water at 63 °C and boiling water at 93 °C for 3 h. The green and simple synthesis of HBPCA resins and their excellent properties provide a novel strategy for preparing biomass-based adhesives. Graphical abstract: Image 1 Highlights: Strategy for a novel citric acid-based hyperbranched polyester wood adhesives with excellent mechanical strength. Without potential hazard of formaldehyde release. Boiling water resistant super performance adhesives.